Effects of a 6-week stroboscopic training program on specific blocking reaction speed in young volleyball players - Zwierko, M.; Jedziniak, W.; Popowczak, M.; Rokita, A. (Physical Activity Review, 2024)
Background: Although stroboscopic effects are recognized as an effective tool for enhancing information processing in general perceptual-cognitive tasks, research on their transfer to sport-specific skills is limited. This study aims to evaluate the impact of a 6-week stroboscopic intervention on volleyball-specific blocking reaction speed. Additionally, it analyzes the variation in explosive leg strength as a potential factor influencing the effectiveness of volleyball blocking.